Zwicky Transient Facility and Globular Clusters: The Period–Luminosity and Period–Wesenheit Relations for Anomalous Cepheids Supplemented with Large Magellanic Cloud Sample - Chow-Choong Ngeow; Anupam Bhardwaj; Matthew J. Graham; Steven L. Groom; Frank J. Masci; Reed Riddle (The Astronomical Journal, 2022)
We present the first gri -band period–luminosity (PL) and period–Wesenheit (PW) relations for the fundamental mode anomalous Cepheids. These PL and PW relations were derived from a combined sample of five anomalous Cepheids in globular cluster M92 and the Large Magellanic Cloud, both of which have distance accurate to ∼1% available from literature. Our g -band PL relation is similar to the B -band PL relation as reported in previous study. We applied our PL and PW relations to anomalous Cepheids discovered in dwarf galaxy Crater II, and found a larger but consistent distance modulus than the recent measurements based on RR Lyrae. Our calibrations of gri -band PL and PW relations, even though less precise due to small number of anomalous Cepheids, will be useful for distance measurements to dwarf galaxies.